Palliative- and non-palliative indications for glucocorticoids use in course of immune-checkpoint inhibition. Current evidence and future perspectives. (January 2021) - Marinelli, Daniele; Giusti, Raffaele; Mazzotta, Marco; Filetti, Marco; Krasniqi, Eriseld; Pizzuti, Laura; Landi, Lorenza; Tomao, Silverio; Cappuzzo, Federico; Ciliberto, Gennaro; Barba, Maddalena; Vici, Patrizia; et al.
Highlights: Glucocorticoid (GC) prescription is frequent in advanced cancer patients. GC usage may affect clinical outcomes of immunotherapy (IT). In advanced cancer patients treated with IT, palliative indications to GC use may relate to inferior clinical outcomes. Abstract: Immune-checkpoint inhibitors significantly reshaped treatment landscapes in several solid tumors. Concurrently with disease-oriented therapies, cancer patients often require proper management of drug-related adverse events and/or cancer-related symptoms. Glucocorticoids (GC) are a cornerstone of symptom management in advanced cancer care and in the management of immune-related adverse events (irAEs) due to immune-modulating therapies. Moreover, GC are often administered in patients with autoimmune diseases (AID), either alone or in combination with other treatments. While handling of irAEs with GC is supported by multiple guidelines, it is unclear whether GC administration because of pre-existing AID or because of palliative needs is associated with inferior outcomes in cancer patients treated with immune-checkpoint inhibitors (ICIs). When globally considered, the available evidence seems to orient towards less favorable survival outcomes when GC administration is driven by a palliative intent. Conversely, steroid administration for non-palliative intent seems to be associated with stable or negligibly reduced survival outcomes.